2019
DOI: 10.1016/j.carj.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interface Sign and Diffusion-Weighted Magnetic Resonance Imaging in Differential Diagnosis of Exophytic Renal Masses

Abstract: Purpose We aimed to investigate the role of interfaces of exophytic solid and cystic renal masses on magnetic resonance imaging (MRI) and the added value of diffusion-weighted imaging in differentiating benign from malignant lesions. Methods The Institutional Review Board approved this retrospective study, and informed consent was waived. A total of 265 patients (109 [41%] women and 156 [59%] men) with a mean age of 57 ± 12 (standard deviation) years were enrolled in this study. Preoperative MRI (n = 238) exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Verma 9 showed an angular interface was a strong predictor of an exophytic AML or a cyst on MRI. Likewise, Kulali 8 showed an angular interface was never present with RCC on MRI and was only seen with benign lesions. In fact, of their 192 malignant lesions, all 192 (or 100%) were round and none had an angular interface.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Verma 9 showed an angular interface was a strong predictor of an exophytic AML or a cyst on MRI. Likewise, Kulali 8 showed an angular interface was never present with RCC on MRI and was only seen with benign lesions. In fact, of their 192 malignant lesions, all 192 (or 100%) were round and none had an angular interface.…”
Section: Discussionmentioning
confidence: 92%
“…Other imaging features of these exophytic renal masses have been studied with CT or MRI to help distinguish between benign entities, such as AMLs or renal cysts, from RCCs. Some of the features that have been analyzed include an angular interface, often occurring more commonly with AMLs or renal cysts rather than RCCs, with MRI 8,9 . Others have found that for exophytic renal masses, the “overflowing beer” sign has been helpful in distinguishing fat‐poor AMLs from RCCs on CT 7 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations